Albert Ellis's irrational beliefs in students from a private university in East Lima - De la Cruz Contreras, Freddy Pablo (2017)
Irrational beliefs were studied in a sample of 230 students of the first year of psychology of a private university of Lima East. Through a transectional design of comparative descriptive type, it was used the test of Irrational Belief Inventory of Albert Ellis (1980) which was translated into Spanish by Navas, it also was taken a sociodemographic file to know the characteristics that the students present research subject. It was found there is no statistically significant differences in the presence of irrational beliefs in those students according to the parents’ gender, age, marital status, place of origin, as well as in their work situation.